Islamic Views on Shifting Cultural Values in the Nyongkolan Tradition in Lombok - Aulia Iswaratama (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
This research is a form of qualitative research that explains the nyongkolan tradition in Lombok. Qualitative research is research that produces descriptive data such as written words resulting from observing people's behavior. This research focuses on the shift in cultural values and religious values in the Nyongkolan traditional ceremony due to changing times. This tradition has existed for a long time and is a heritage that is guarded and preserved and used as an activity or routine by the people of Lombok. Through this tradition, people hope to receive blessings and a form of community gratitude as well as a sacred form for the wedding that is carried out and as a closing in a series of wedding events in Lombok.